2021
DOI: 10.1590/1980-0037.2021v23e73039
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue and depression improvements on breast cancer survivors practitioners of strength training

Abstract: Due to the high incidence of breast cancer worldwide, it is important to research and understand the physiological and psychological effects of this disease, like fatigue, depression, and capacity to do daily life tasks and how they modify physical activity. This study aimed to analyze the effects of strength training practice on physical fatigue (IMF-20), depression (Beck questionnaire), handgrip strength, and functional performance (time up and go). The sample was composed of 17 women breast cancer survivors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
1
0
1
Order By: Relevance
“…Our previous study indicated that the improvement of depression was evidenced mainly in breast cancer survivors with a higher level of physical activity in the leisure/time commuting domain [ 48 ]. Breast cancer survivors who participated in a regular program of strength training for six months demonstrated lower depression symptoms and physical fatigue when compared to participants who did not practice strength training [ 49 ]. In addition, a recent meta-analysis indicated that mind-body exercise (i.e., activities that combine body movement with mental concentration) may benefit physical fitness, sleep quality, depression, and anxiety [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study indicated that the improvement of depression was evidenced mainly in breast cancer survivors with a higher level of physical activity in the leisure/time commuting domain [ 48 ]. Breast cancer survivors who participated in a regular program of strength training for six months demonstrated lower depression symptoms and physical fatigue when compared to participants who did not practice strength training [ 49 ]. In addition, a recent meta-analysis indicated that mind-body exercise (i.e., activities that combine body movement with mental concentration) may benefit physical fitness, sleep quality, depression, and anxiety [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…De acordo com Chaves (2021), para amenizar os efeitos colaterais tardios comumente pelo tratamento ou pela própria doença, reduzindo a fadiga e precavendo a carência de tecido muscular esquelético, propõe-se o treinamento de força (TF) como uma interposição eficiente e segura. Outrossim, cresce a resistência e o desempenho, o TF reprime a fadiga, aumenta as funções cardiovasculares e eleva a síntese proteica.…”
Section: Câncerunclassified